Classical Period Kalam Content of Some Arabic Poems - Süleyman KOYUNCU (Mütefekkir, 2018)
Poetry is an important literary genre in the transmission of thoughts and feelings. Due to this important function, it has been used in different fields/disciplines. In Arabic poems it is seen that many topics related to the science of Kalam are mentioned. We can see the traces of Kalam content in Arabic poem which is praised by Prophet Muhammad. It mentions the aspects such as existence and unity of God, prophecy, death and afterlife, holly word of God, as well as indicating the deeds of humans in relation to this life and the life to come, and the obligation to ensure a balance between the two worlds by practicing the services to God. However, the subjects other than the aforementioned ones also exist for poems. Many other subjects, such as consistency of words and actions of a person, the real reason in acquiring properties, making friendships for God, not having any earthly purposes, and doing the best we can do before death, have been included in the poems. One would wish that all subjects mentioned above could be included in this article; however, the field of this article does not possess the infinity to include all such subject, thus we have decided to mention only some of the subjects we talked about in this study. While dealing with the existence and unity of God, prophet hood of the prophet Muhammad, death and resurrection and the Poem and Kalam relationship regarding Quran the holly word of the God, we have decided that it was convenient to prepare our article by using the Quran and Sunnah of Prophet and the views of Kalam scholars.